Bücher unter Verdacht : NS-Raub- und Beutegut an der SUB Göttingen - Bartels, Nicole (2011)
"Books under suspicion" was the title of an exhibition of the Göttingen State and University Library presenting examples of Nazi looted and looted books from its holdings. The exhibition catalogue not only documents all the objects on display, but also provides information on the historical background in short introductions. Probably almost all academic libraries included books in their collections during the Third Reich that came from confiscated libraries of workers' associations and other organisations, that were stolen by the National Socialists during raids on bookshops and publishing houses and given to libraries, that private individuals had to hand over under duress or that were looted in the occupied territories during the war. Many other examples could be cited. This exhibition catalogue provides an insight into the contemporary practice of a university library in dealing with Nazi looted books, as they are called today. (translated with DeepL)...